Enantiomeric pairs of meroterpenoids with 11/5/6 spiro-heterocyclic systems from Hypericum kouytchense. Issue 23 (1st November 2022) - Huang, Jin-Chang; Sheng, Li; Zong, Jian-Fa; Zhou, Yu-Bo; Li, Jia; Hou, Ai-Jun
Abstract : Undescribed enantiomeric pairs of acylphloroglucinol related meroterpenoids with 11/5/6 spiro-heterocyclic systems were isolated from Hypericum kouytchense . Abstract : Six undescribed enantiomeric pairs of acylphloroglucinol related meroterpenoids, (±)-hyperkouytins A–F (1a /1b–6a /6b ), were isolated from Hypericum kouytchense . These enantiomers were acquired by chiral-phase HPLC, and their structures were established using spectroscopic and X-ray crystallographic data. These compounds incorporate a rare 11/5/6 heterocyclic system featuring a 1-oxaspiro[4.10]pentadecane moiety. Compounds 1b and 3a exerted antiproliferation activity against the MV-4-11 cell line.